1998
DOI: 10.1007/bf03185457
|View full text |Cite
|
Sign up to set email alerts
|

On amplification of radiation emitted from the excited autoionizing state of the H2 molecule in the presence of incoherent pumping to the lowest autoionizing state

Abstract: We have shown that the amplification without population inversion (AWOPI) from the first excited autoionizing (AI) state of the lL;g symmetry of the H 2 molecules can be obtained when the lowest AI state of the lL;g symmetry is pumped incoherently. We have considered a resonant two-photon transition scheme from the ground X1L;g(v O,j 1) state to the ionization continuum embracing the two AI states (the lowest and the first excited autoionizing states) of the 1 L;g symmetry via the resonant intermediate B 1 L;u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We found that the values of populations and coherences obtained by solving the density matrix equations numerically at large time are in good agreement with the values obtained from the exact expressions in the steady state limit. However, results obtained with first-order approximation agree with the numerical results only when Ω G. AWI were studied theoretically either by choosing different parameters for the process [12,13] or in real systems like atoms [14,15] and molecules [3][4][5][16][17][18]. The presence of rotational and vibrational states makes the study of LWI/AWI fascinating in molecules as these states influence the process of inversionless lasing.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…We found that the values of populations and coherences obtained by solving the density matrix equations numerically at large time are in good agreement with the values obtained from the exact expressions in the steady state limit. However, results obtained with first-order approximation agree with the numerical results only when Ω G. AWI were studied theoretically either by choosing different parameters for the process [12,13] or in real systems like atoms [14,15] and molecules [3][4][5][16][17][18]. The presence of rotational and vibrational states makes the study of LWI/AWI fascinating in molecules as these states influence the process of inversionless lasing.…”
Section: Introductionmentioning
confidence: 91%
“…However, the lasers used should have bandwidth short enough to avoid resonant excitation from other vibrational levels. Earlier, our group has studied AWI in H 2 molecule using resolvent operator technique [3][4][5], in which the dependence of gain on the choice of different vibrational levels was also shown considering the effect of two-photon near-resonant transitions to autoionizing states (the upper lasing level). In a recent calculation [20] on three-level ladder, V and Λ system in H 2 and Li 2 molecules we have shown that AWI can be obtained in VUV, and in violet region respectively from the first excited Rydberg state when two of the levels are coupled by a strong coherent field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation